"BRUTOR DE TENIR PELL": SEXUALITAT, DESIG I GÈNERE EN LES POETES DE L'ÚLTIMA DÈCADA. (June 2020) - MATAS, MERITXELL
Abstract : Poetics of the body is predominant among the female Catalan authors of the second decade of the twenty-first century, notably Maria Sevilla, Lucia Pietrelli, Raquel Santanera and Maria Isern. From the early 2000s, beginning with Mireia Calafell's Poètiques del cos (2006), there has been a growing tendency to characterize contemporary poetry in Catalan by female authors as part of this genre. This paper reflects on this tendency to 'braid the verses with the body', as Maria-Mercè Marçal would say, paying special attention to sexuality and gender. Further, the paper focuses on the relationship of these contemporary female poets with other authors and with some relevant feminist theories, resulting in an eclectic variety of texts. Their poems show how desire and eroticism are the political tools used to reclaim female bodies and to deflect them away from the male gaze, and how this is achieved by placing the emphasis on the body's physical responses.